The Constitutional Development of Hungary After 1918 - Szabó, István (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Before 1918, Hungary had a “historical constitution”. The structure of the constitutional system was not included in a single constitutional chart, instead it was determined by separate laws passed over the centuries in addition to customary law. However, the military collapse of 1918 started a revolutionary wave in Hungary, which caused a significant break in the development of the organic constitution. The revolution radicalized, followed by foreign military occupation. The National Assembly, convened in January 1920, restored the pre-1918 constitutional order, making the country a kingdom again. However, the constitutional system contained a number of unique features. The king, crowned before 1918, did not return to the throne, but was replaced by a governor. The second chamber of the parliament was also significantly reorganized, but the most controversial point in the whole system was the right to vote. Although it has been significantly widened, it still had shortcomings compared to the expectations of the age. The most striking was the re-introduction of open voting. After 1945, with the introduction of the republican form of government, a democratic experiment took place. However, the Soviet occupation made it impossible to build a democratic state In 1949, a Soviet-style constitution was issued, which meant the establishment of a dictatorship. This state order did not adopt the basic institutions of the rule of law, nor did it provide the minimum requirements of legal certainty for its citizens. In 1989/90, constitutionality was restored, which had already taken on the expectations of the age. However, this was still achieved by amending the 1949 constitution. Although it did not mean a significant change in its content, in 2011 the Parliament passed a new Fundamental Law, which permanently broke with the pre-1989 constitutional order. KEYWORDS: governor, upper chamber, open voting, kingdom, republic, dictatorship, restoration of constitutionalism, Fundamental Law.